As contribuições do dialogismo de bakhtin e do signo em umberto eco para o ensino de língua estrangeira - Silva, Sandra Regina [UNESP]; Magnoni, Antonio Francisco [UNESP] (My University, 2014)
This article discusses the dialogism in Mikhail Bakhtin and the grounds of the linguistic sign in Umberto Eco, with the intention to use the themes and authors, to support the teaching-learning methodologies of foreign language (English and Spanish) at the public school of São Paulo state. The conceptual approach of the two authors allows us to infer that learning a foreign language is effected by the appropriation of utterances and cultural knowledge, pedagogical concept that confronts the traditional method used in the São Paulo school, which is based mainly on grammar teaching and lexicons. The paper derives the theoretical research used to support a dissertation, posing and evaluates preliminary, the integration of traditional theaters in foreign language in public schools, with digital environments (in online courses), and also the educational effects -the use of audiovisual material at the classroom and online learning.

O presente artigo discute o dialogismo em Mikhail Bakhtin e a fundamentação do signo linguístico em Umberto Eco, com a intenção de utilizar os referidos temas e autores, para subsidiar as metodologias de ensino-aprendizado de língua estrangeira (inglês e espanhol) na rede de ensino público paulista. A abordagem conceitual dos dois autores nos permite inferir que o aprendizado de uma língua estrangeira é efetivado pela apropriação de enunciados e de conhecimento cultural, uma concepção pedagógica que confronta o método tradicional utilizado no ensino paulista, que é baseado, principalmente, no ensino de gramática e de léxicos. O artigo deriva da pesquisa teórica utilizada para subsidiar de uma dissertação de mestrado, que levanta e avalia preliminarmente, a integração das salas tradicionais de língua estrangeira nas escolas de ensino público, com ambientes digitais (em cursos on-line), e também os efeitos didático-pedagógicos da utilização de material audiovisual presencial e online.
The contributions of the dialogism in bakhtin and sign on umberto eco for the teaching of foreign language
Keywords: Face-virtual school; English; Spanish; EVESP; Escola presencial-virtual; Inglês; Espanhol; EVESP